REFLECŢII ASUPRA PROCEDURII DE MEDIERE ÎN SOLUŢIONAREA CONFLICTELOR COMUNITARE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2011)
Mediation is an optional way of solving the conflicts in a peaceful way. It is done with the help of the third person specialized as a mediator, in neuter conditions, impartiality and confidentiality. Mediation is based on the confidence of the both sides accorded to the mediator. This fact facilities the negotiations between them and supports it for solving the conflict, obtaining a reciprocal, advantageous, efficient and durable solution. In fact, mediation is a way of noble justice. It saves time, emotions and finance. The mediator with the ability of a psychologist speaks with the sides, finds the true interest of these and maintains always the confidentiality and impartiality. He could find the most proper solution according to the both interests of the sides, without imposing them. The mediator is not a judge, he accept the solution, or to find other variants with the mediator, or to withdraw from mediation. The mediation is an alternative way of solving the disputed issues. It has its own history. It appeared from the practical activity of the ombudsman, first of all in USA, Scandinavian countries, Germany and France. It was established as an organization in EU, through the art. 138 E, from the Treaty of Maastricht. The European mediator it is expressed a new concept of the relationship between EU and its citizens. From 2006, it was assumed by Romania and it follows to be implemented in Republic of Moldova too.